Effectiveness of biopesticides against brown planthopper (Nilaparvata lugens) in paddy cultivation - Ramli, N.H. (Elsevier B.V., 2018)
The brown planthopper (BPH) causes serious damage to rice by sucking rice sap, ovipositing in rice tissues, and transmitting a number of rice diseases during its long-distance migration that severely affect the productivity of paddy. Thus, the aim of this study is to investigate the effectiveness of biopesticides against BPH population. BV500WS is used at the early stage of paddy cultivation for growth enhancement meanwhile BV612EC is used a week after the liberation of BPH for crop protection. Three conditions were adopted as follows which are T1 where the paddy was sprayed using BV500WS and BV612EC to study the effectiveness of both types of biopesticides, T2 where the paddy was sprayed using BV500WS only and C1 where the paddy was cultivated without any pesticide application as control. BPH was released twice on day 46 and 59 of paddy cultivation. Reduction of BPH population with up to 100 mortality rate was observed with the application of two types of biopesticides at T1 resulting in the highest number of remaining tillers with 68.56. Although severely affected by BPH, T2 was able to has comparable number of remaining tillers as C1 which was 46.24 and 49.65 respectively. These results showed that two types of biopesticides were more effective in reducing BPH compared to one type of biopesticide. Â© 2018 Elsevier B.V.